Evapotranspiration-Based Irrigation for Agriculture: Implementing Evapotranspiration-Based Irrigation Scheduling for Agriculture - Haimanote K. Bayabil; Sandra M. Guzman; Isaya Kisekka; Kati W. Migliaccio; Michael D. Dukes; Jonathan H. Crane; Bruce Schaffer (EDIS, 2019)
This publication is part of a series on evapotranspiration (ET)-based irrigation scheduling in agriculture and outlines step-by-step procedures for implementing a “smart” ET-based irrigation schedule and a do-it-yourself irrigation schedule. Revised April 2019 with Haimanote K. Bayabil and Sandra M. Guzman.